Introduction to AutoCAD 2016 2D and 3D design - Palm, Bernd S.; Yarwood, A. (Alfred), 1917- (Routledge, Taylor & Francis Group, 2015)
A comprehensive, step-by-step introduction to the latest release of AutoCAD. Covering all the basic principles and acting as an introduction to 2D drawing, it also contains extensive coverage of all 3D topics, including 3D solid modelling and rendering.